2016
DOI: 10.18357/ijih111201616013
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Culturally Respectful Cancer Education Through Digital Storytelling

Abstract: Cancer is the leading cause of mortality among Alaska Native people. Over half of Alaska Native people live in rural communities where specially trained community members called Community Health Aides/Practitioners (CHA/Ps) provide health care. In response to CHA/Ps’ expressed desire to learn more about cancer, four 5-day cancer education and digital storytelling courses were provided in 2014. Throughout each course, participants explored cancer information, reflected on their personal experiences, and envisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
1
31
0
1
Order By: Relevance
“…Resulting digital stories are short, first person visual narratives that synthesize digital images, audio recordings of a first person, told story, music, and text to document personal experiences [10]. Digital storytelling combines the past methods of storytelling with the recent advances in technology and carries people through the past, present and future [11].…”
Section: Types Of Platform For Storytellingmentioning
confidence: 99%
“…Resulting digital stories are short, first person visual narratives that synthesize digital images, audio recordings of a first person, told story, music, and text to document personal experiences [10]. Digital storytelling combines the past methods of storytelling with the recent advances in technology and carries people through the past, present and future [11].…”
Section: Types Of Platform For Storytellingmentioning
confidence: 99%
“…All 16 studies explored and reported the perceived impact of digital storytelling on the learning of health professionals using one or two of the following data collection strategies: self-reported questionnaires, standardized questionnaires, focus groups, or interviews. Of these 16 studies, five (31.3%) focused exclusively on health professionals’ learning from the creation of their own digital stories as part of a formal educational experience [ 9 , 23 , 25 , 32 , 33 ]. In these five studies, digital storytelling positively impacted the health professionals’ learning.…”
Section: Resultsmentioning
confidence: 99%
“…In the creation of these stories, health professionals drew on their own personal experiences with cancer, as well as factual knowledge about the disease. They found that the creation experience, along with their abilities to share their digital stories with their family members and communities, motivated them to increase their own knowledge and understanding of cancer, as well as changed their attitudes towards cancer and their reactions to those who had experienced it [ 32 , 33 ]. Gazarian, Fernberg, and Sheehan [ 25 ], on the other hand, asked nursing students to create a digital story about an ethical concern encountered in practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations